2018
DOI: 10.13031/trans.12980
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for Moisture Analytical Tests Used in Cotton Ginning Research

Abstract: Abstract. Cotton post-harvest processing research requires moisture content determination for seed cotton, cottonseed, and lint. Methods for determining moisture content have changed and are no longer consistent between laboratories. This research compared standard procedures documented in 1972 and those currently practiced for finding moisture content by oven drying, and quantified the variability. Seed cotton from four modern cultivars (ranging from 9.4% to 36.8% foreign matter), lint, and cottonseed were br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This approximation method is easier because it does not require expensive ovens, is more convenient, and for most cases, the bias is consistent and within 0.5% MC ,which is sufficient for gin operations. The reference for weighing hot outside the oven is provided in Funk et al (2018). Byler's (2004a) test reported that seven, 1-g samples were found to result in the same confidence in MC values as three, 20-g specimens, while consuming 12% as much cotton.…”
Section: Gravimetric Standard Methods For Moisture Content Determinat...mentioning
confidence: 99%
“…This approximation method is easier because it does not require expensive ovens, is more convenient, and for most cases, the bias is consistent and within 0.5% MC ,which is sufficient for gin operations. The reference for weighing hot outside the oven is provided in Funk et al (2018). Byler's (2004a) test reported that seven, 1-g samples were found to result in the same confidence in MC values as three, 20-g specimens, while consuming 12% as much cotton.…”
Section: Gravimetric Standard Methods For Moisture Content Determinat...mentioning
confidence: 99%
“…Two seed cotton sub-samples per gin lot (500 g each) were collected from the wagon before seed cotton cleaning and at the feeder prior to ginning for fractionation and gravimetric moisture content analysis using the method described by Funk et al. 33 Two lint sub-samples per gin lot (500 g each) were collected before and after the lint cleaner used in each ginning system for high volume instrument (HVI) and Advanced Fiber Information System (AFIS) fiber analysis. Since the lint cleaning systems used with the HSRG and saw ginning systems were different, fiber analysis before and after lint cleaning was conducted to highlight differences in the ginning systems alone (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Lint was valued based on the results of HVI analysis and all years were standardized to the 2012 Commodity Credit Corporation Loan Chart. 36 Gravimetric moisture content 33 was also measured on the lint sub-samples collected after lint cleaning. All seed cotton fractionation was conducted by USDA ARS personnel at the Cotton Production and Processing Research Unit in Lubbock, Texas, while all gravimetric moisture content analyses were conducted by USDA ARS personnel at the Southwestern Cotton Ginning Research Unit in Mesilla Park, New Mexico.…”
Section: Methodsmentioning
confidence: 99%
“…Seed cotton samples (150 g each) collected from the overflow hopper were placed in plastic bags for foreign matter analysis by fractionation (Shepherd, 1972). Additional seed cotton samples (50 g each) were also collected from the overflow hopper and placed in air-tight containers for moisture content determination by oven method (Funk et al, 2018).…”
Section: Test Proceduresmentioning
confidence: 99%